PERBANDINGAN EFEKTIVITAS MCKENZIE CERVICAL DENGAN CHIN TUCK TERHADAP FORWARD HEAD POSTURE PADA REMAJA PONPES - Muhammad Abror; Angria Pradita; Nurul Halimah; Sartoyo Sartoyo; Mohammad Asy'ari; Muhamad Khozin (Kieraha Medical Journal, 2026)
Forward Head Posture (FHP) is a postural disorder commonly found among Islamic boarding school students (santri) due to prolonged static sitting activities such as reading, memorizing, and studying. This study aimed to determine the difference in effectiveness between McKenzie Cervical Exercise and Chin Tuck Exercise on improving Forward Head Posture through Craniovertebral Angle (CVA) values in students at Yambu'ul Quran Islamic Boarding School, Kediri. This study used a quasi-experimental design with a two group pre-post test approach involving 30 male respondents aged 12–18 years, divided into two groups: the McKenzie Cervical Exercise group (n=15) and the Chin Tuck Exercise group (n=15). CVA measurements were performed using the AI Posture Evaluation and Correction System (APECS) application. Normality was tested using the Shapiro-Wilk test, within-group analysis was conducted using the Wilcoxon Signed Rank Test, and between-group comparison was analyzed using the Mann-Whitney U Test. The results showed that McKenzie Cervical Exercise increased the median CVA value from 47.0° to 50.0° (p=0.007), while Chin Tuck Exercise increased the median CVA value from 46.0° to 49.0°. There was a significant difference in effectiveness between the two interventions, where McKenzie Cervical Exercise proved to be more effective than Chin Tuck Exercise in improving CVA values in santri with Forward Head Posture (p<0.05).